A case of herpes zoster oticus with multiple cranial nerve palsy - Sahoo, Debananda; Patro, Shubhransu; Khora, Pankaj K.; Panda, Udaya N. (International Journal of Advances in Medicine, 2016)
Herpes zoster oticus (HZO) otherwise called as Ramsay Hunt syndrome is a rare complication due to reactivation of the herpes zoster virus in the geniculate ganglion of facial nerve presenting with vesicular eruptions over external ear along with severe otalgia and LMN type of 7th cranial nerve palsy. This syndrome often misdiagnosed because of absence of these symptoms. About 12% of all peripheral facial nerve palsies are caused by varicella zoster virus. The occurrence rate of associated cranial polyneuropathy has been reported to be 1.8-3.2% and cranial nerves VII, VIII, IX and X are the ones most commonly affected. Here, we present a case of Ramsay Hunt syndrome with cranial polyneuropathy. The patient was treated with antiviral and oral steroid and the symptoms were improved.